(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
This article will consider the possible combination of catalytic cracking and metathesis processes and the calculation of economic efficiency to obtain ethylene from C3+ olefins by process calculation in Aspen HYSYS software.